Penerapan Latihan Batuk efektif Pada Pasien Anak Asma Bronkial dengan Bersihan Jalan Nafas Tidak Efektif di RS X Provinsi Sumatera Selatan - Sakinah, Wahyu; Afdhal, Fitri; Wulandari, Ria; Romadhon, Muhammad (JURNAL KESEHATAN TERAPAN, 2025)
Bronchial asthma is a chronic inflammation of the respiratory tract that affects the trachea and bronchi and is very common. Exposure to various stimuli can lead to airway hyperresponsiveness, causing symptoms such as shortness of breath (wheezing), chest tightness, and coughing. This inflammation is closely associated with those responses.The objective of this study was to implement nursing care for patients with respiratory system disorders, specifically bronchial asthma with the main nursing diagnosis of ineffective airway clearance. The population in this study consisted of all inpatients in the internal medicine ward of Hospital X, South Sumatra Province, who were diagnosed with bronchial asthma during the research period. From this population, two patientswho met the inclusion criteria (diagnosed with bronchial asthma and experiencing ineffective airway clearance) were selected as the samples.This research used a descriptive method with a case study approach. The main intervention applied was effective coughing exercises along with pharmacological therapy using bronchodilators. Data collection techniques included interviews, observations, physical examinations, and documentation studies.The results showed that both patients initially complained of productive cough and shortness of breath. After three days of intervention using effective coughing exercises, bronchodilator administration, and the implementation of SLKI (Indonesian Nursing Outcome Standards) and SIKI (Indonesian Nursing Intervention Standards), the problems were resolved. The main nursing diagnosis of ineffective airway clearance was successfully addressed.